Evaluation of demographic component of countries’ economic security - Hrybinenko, Olha; Bulatova, Olena; Zakharova, Olha (Business, Management and Economics Engineering, 2020)
Purpose – The article is aimed at evaluation of the patterns of demographic processes development in terms of their impact on shaping the level of countries’ economic security. Research methodology – The study is based on a multidimensional estimation technique, which proposes the development of an integral indicator of the demographic component of countries’ economic security. Stochastic research methods, in particular the t-test method, were used to identify and justify different hazard zones. Findings – On the basis of the formed sample of the countries, the integral indices of the level of the demographic component of countries’ economic security for the period of 2000–2018 were calculated. The thresholds of demographic security indicators were identified and reasoned; the countries’ security risks by demographic indicators were assessed; systematisation of countries according to the level of the demographic component of security was provided. Research limitations – It is proposed to include ten indicators in the structure of the index of the demographic component of economic security; these indicators characterise different aspects of the demographic processes development. However, this is not a complete list of possible valuation indicators. This determines the necessity of further studies in terms of justifying the advisability of including various parameters and assessing the degree of their importance in the structure of the demographic security index. Practical implications – The practical value of the results of the comprehensive analysis of the demographic processes development in the system of ensuring countries’ economic security is the possibility of identifying real or potential threats to the sustainable social and economic development of countries and regions of the world. Originality/Value – The authors’ improved methodology for assessing the level of economic security based on the demographic component consideration, taking into account the system of proposed indices, allows to assess the level of security, to monitor its changes and to identify factors that pose risks not only for one country but also for groups of countries both in regional dimension and in terms of the level of their development.